Acute Postpartum Pulmonary Edema in a 32-Year-Old Woman Five Days after Cesarean Delivery - Khan, Masuda Islam; Ahmed, Nasir Uddin; Khan, Md. Shahabuddin (Journal of Enam Medical College, 2013)
Acute dyspnea after pregnancy is a rare presentation, and a number of important conditions may accompany it. Pulmonary embolism, amniotic fluid embolism, pneumonia, aspiration and pulmonary edema are some of the potential causes that must be considered. The percentage of pregnancies that are complicated by acute pulmonary edema has been estimated 0.08%. The most common contributing factors include the administration of tocolytic agents, underlying cardiac disease, iatrogenic fluid overload and preeclampsia. Here we report a case of 32- year-old woman of 5th postpartum day following lower uterine cesarean section with acute dyspnea from her first pregnancy who was admitted in coronary care unit with history of one episode of raised blood pressure 160/90 mm Hg and cough on 1st postoperative day. Clinical examination and relevant investigations explored that it was a case of bilateral pulmonary edema. Patient was kept in ventilator and was treated with nitroglycerine (GTN), frusemide and ACE inhibitor. After diuresis, considerable improvement was observed in her respiratory status. From the 4th day, the patient became hemodynamically stable and was weaned off the ventilator. After five days, all the biochemical parameters became normal and she had no dyspnea. Journal of Enam Medical College; Vol 3 No 2 July 2013; Page 113-116 DOI: http://dx.doi.org/10.3329/jemc.v3i2.16135